The Effect of Pedagogical Practices Employed by “Connecting Classrooms” Teachers’ on the Learning Outcomes of Elementary Level Students - Shan, Rehana Ali; Nawaz, Muhammad Hameed (Pakistan Languages and Humanities Review, 2022)
Teachers’ training is a vital component of ensuring quality education. There are a number of organizations that work to promote teachers’ education. The British Council's Connecting Classrooms programme is a global initiative, in Punjab, this programme has been implemented for public sector schools in partnership with School Education Department since 2015. The present study was designed to investigate the effect of this program on teachers’ pedagogical practices and students’ learning. Researcher employed Causal Comparative design. It was delimited to the public sector’s schools of Lahore, Multan, and Rawalpindi. Population of the study was comprised on elementary portions of schools, their teachers, and students. Multistage sampling technique was used. The sample was consisted of 134 schools, 536 teachers, and 2680 students. During study, three instruments were used, a knowledge Questionnaire, an observation sheet, and PEC papers. The study concluded that teachers’ who got the chance to work on international ethos, their pedagogical practices and students’ performance were comparatively better.